Hospital at home for patients with acute exacerbations of chronic obstructive pulmonary disease: systematic review of evidence - Ram, Felix S F (BMJ Publishing Group Ltd., 2004)
Objectives To evaluate the efficacy of hospital at home schemes compared with inpatient care in patients with acute exacerbations of chronic obstructive pulmonary disease (COPD). Design A systematic review of randomised controlled trials. Main outcome measure Mortality and readmission to hospital. Results Seven trials with 754 patients were included in the review. Hospital readmission and mortality were not significantly different when hospital at home schemes were compared with inpatient care (relative risk 0.89, 95% confidence interval 0.72 to 1.12, and 0.61, 0.36 to 1.05, respectively). However, compared with inpatient care, hospital at home schemes were associated with substantial cost savings as well as freeing up hospital inpatient beds. Conclusions Hospital at home schemes can be safely used to care for patients with acute exacerbations of COPD who would otherwise be admitted to hospital. Clinicians should consider this form of management, especially as there is increasing pressure for inpatient beds in the United Kingdom.